1979
DOI: 10.1042/cs0560083
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Human Serum Ferritin to Concanavalin A

Abstract: 1. A high proportion of the ferritin in normal serum binds to concanavalin A. Binding is prevented by the addition of alpha-D-methylglucoside to the reaction mixture. 2. Ferritin in extracts of normal heart, liver and spleen or serum ferritin from patients with massive hepatic necrosis does not bind to concanavalin A. 3. Isoelectric focusing of preparations of serum ferritin from patients with primary haemochromatosis shows that the ferritin fraction binding to concanavalin A consists, predominantly, of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(47 citation statements)
references
References 7 publications
0
46
0
1
Order By: Relevance
“…10 Serum was incubated for two hours at room temperature with Concanavalin A Sepharose 4B on a roller mixer. The sample was then centrifuged at 3000 rpm for 15 min and unbound ferritin was recovered in the supernatant and assayed using an immunoassay (DadeBehring).…”
Section: Measurement Of Ferritin Glycosylationmentioning
confidence: 99%
“…10 Serum was incubated for two hours at room temperature with Concanavalin A Sepharose 4B on a roller mixer. The sample was then centrifuged at 3000 rpm for 15 min and unbound ferritin was recovered in the supernatant and assayed using an immunoassay (DadeBehring).…”
Section: Measurement Of Ferritin Glycosylationmentioning
confidence: 99%
“…When there is tissue damage, direct release of cytosolic ferritin through damaged cell membranes becomes important. In patients with ferritinaemia resulting from necrosis of the liver, the plasma ferritin shows reduced binding to concanavalin A (67). Findings in patients with haemophagocytosis or in the early stages of haemochromatosis confirm the importance of phagocytic cells (see below).…”
Section: Origin Of Serum Ferritin and Its Clearance From The Circulationmentioning
confidence: 74%
“…It was suggested by Prieto et al (66) that the ratio of serum ferritin to aspartate aminotransferase activity might provide a good index of liver iron concentration. Glycosylated ferritin concentrations might be related directly to storage iron concentrations, while the concentration of non-glycosylated ferritin would relate to the degree of liver damage (67). However neither the ferritin:aspartate aminotransferase ratio (68,69) nor the measurement of glycosylated ferritin concentration (33,70) have proved to be any more reliable than the simple measurement of serum ferritin concentration as an index of liver iron concentration.…”
Section: Serum Ferritin and Liver Diseasementioning
confidence: 99%
“…Worwood et al (1979) found that only the acidic isoferritins of human serum bound to Con A while the most basic isoferritins did not. Halliday et al (1979) reported that the plasma half-life of ferritin which was bound to Con A was approximately twice that of ferritin which did not bind.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomena may be due to the fact that the most plasma proteins become glycosylated during secretion into the plasma. Such a process may be important in determining the properties of circulating ferritin (Worwood et al, 1979 …”
Section: Discussionmentioning
confidence: 99%